Theoretical and methodological principles of building a competitive enterprise strategy - І. Bozhydai (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article is devoted to theoretical and methodological principles of competitive enterprise strategy. The process of forming a competitive strategy requires a comprehensive approach, a sound analytical stage, and must comply with certain principles. The author summarized the basic principles of formation of competitive strategy, and in accordance with them, proposed a structural and logical scheme of using the tools of formation of competitive strategy of the enterprise. The basic methods such as matrix, benchmarking, PEST-, SWOT-SPECE- and cluster analyzes are selected as the methodological base. The result of which are indicators of analysis of the competitive environment, the internal environment of the enterprise, clustering criteria, the number of clusters, the corresponding quadrants of the matrix of strategies with promising development vectors, the list of measures and indicators for a certain enterprise aimed at stabilizing / improving its competitive position in the market or level competitiveness.